Does osseointegration occur around nonprimary stabilized titanium implants? A histomorphometric analysis - Toy, V. E.; Sabanci, A. C.; Dundar, S.; Bozoglan, A. (Ariesdue Srl, 2023)
Aim The aim of this study was to analyze the levels of bone implant contact (BIC) and bone area between the threads (BABT) of primary and nonprimary stabilized titanium implants histologically in rats. Materials and methods Fourteen Sprague-Dawley rats were categorized as two groups: primary (PS) and nonprimary stabilization (NPS) groups. Totally, 14 titanium implants with machined surfaces were integrated into the tibial bones of the rats with and without primary stabilization in the PS and NPS groups, respectively. After 12 weeks of healing, the rats were sacrificed, block sections were acquired for histological analysis. Results The BIC ratios (%) in the PS and NPS groups were 53.23 +/- 5.65% and 40.79 +/- 5.59%, respectively and was significantly higher in the PS group as compared with that in the NPS group (P<0.05). The mean BABT ratios (%) in the PS and NPS groups were 55.71 +/- 7.32% and 37.14 +/- 2.67% respectively. The BABT ratio (%) was significantly higher in the PS group than in the NPS group (P<0.05). Conclusion The results suggest that osseointegration may occur despite the absence of primary stability at the end of a 12-week healing period but primary stabilization at the time of installation appears to be critical in achieving maximum BIC and BABT.
Keywords: Dental implant; Histomorphometric analysis; Osseointegration; Primary stabilization